War, peace and organizational ethics - Harris, Howard; Schwartz, Michael (Emerald Publishing Limited, 2020)
Research in Ethical Issues in Organizations (REIO) is a doubleblind, peerreviewed series that publishes rigorous academic research into organizational ethics from a wide variety of disciplinary perspectives including, but not limited to, business management, philosophy, sociology, psychology, religion, accounting, and marketing. In this volume, War, Peace and Organizational Ethics, expert contributors draw upon philosophers such as Aristotle, Alasdair MacIntyre, and Emmanuel Levinas in order to explore how the ethics of war and peace resonate with organizational ethics. The topics covered include: the role of business in the "War on Terror"; the ethics of robot decisionmaking in military contexts; the use of force in UN peacekeeping missions; John Wooden's conception of moral leadership; the implementation of meaningful change in relation to wellbeing in and outside of work; unethical proorganizational behaviour; forsaking Aristotle's Mean and pursuing the extreme. Ideally suited for researchers and professionals, this book poses questions that go to the very heart of the role organizations play in greater social conflicts, as well as the role that conflict plays in shaping organizations., Short description/annotation, In this doubleblind, peerreviewed volume, expert contributors draw upon philosophers such as Aristotle, Alasdair MacIntyre, and Emmanuel Levinas in order to explore how the ethics of war and peace resonate with organizational ethics.
Introduction -- War, peace and organizational ethics / Michael Schwartz and Howard Harris -- Chapter 1. Levinas and business ethics in the 'war on terror' / Peter McGhee -- Chapter 2. The ten commandments of working robots in organizations: from history to the future of robot ethics, legislation, and management / Issam Kouatli, Rayan Kouatly and Abir Zaarour -- Chapter 3. Closing the gap between promises and outcomes : how moral frameworks can guide the realisation of United Nations deployment objectives / Charuka Ekanayake -- Chapter 4. Visualizing success: the wisdom of John Wooden / Jim Wishloff -- Chapter 5. Rushing fools and wise women: tales for organisations aiming to improve lives / Cécile Rozuel -- Chapter 6. Strong identification, weak ideology, organizational culture or all: unethical pro-organizational behaviour in India / Pratima Verma and Siddharth Mohapatra -- Chapter 7. Forsaking the mean for the extreme: a response to Provis / Michael Schwartz and Debra R. Comer.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: War -- Economic aspects; Peace -- Economic aspects; Political Science -- General; Theory of warfare & military science